Mouse breeding facilities in Argentina: Current state, challenges, and strengths in relation to animal welfare - Resasco, Agustina; Diaz, Silvina Laura (Frontiers in Veterinary Science, 2022)
The science and technology of laboratory animals has come a long way worldwide, but for reasons related to the development of the countries, this journey started later in some Latin American countries, as is the case of Argentina. Without a specific legal framework to conduct animal experimentation, local strengths to promote animal welfare are based on professionals specifically trained in the care of laboratory animals as well as an extended network of ethics committees that ensures compliance with the ethical principles applied to animal experimentation. Nevertheless, there are no updated reports showing welfare indicators in rodent facilities. Therefore, we conducted a survey on mice breeding facilities enrolled in a national record elaborated by the National Ministry of Science. Questions related to four of the Five Domains Model of Mellor, concerning 1) nutrition, 2) physical environment, 3) health, and 4) behavioral interactions with the environment, other animals, and humans, were included as well as information concerning general aspects of the establishments. Data obtained from 25 mice breeder facilities localized all over the country were summarized, providing for the first time a clear picture of the national situation about the welfare of laboratory mice in these establishments. This data will be essential to design future policy as well as for deciding priorities aiming to improve the welfare of mice bred in Argentinian facilities.